Help pleaseeeeee!!!!

Answer: x= 3/7
Step-by-step explanation:
Simplifies to:
9x-9+6-2x=0
7x-3=0
7x=3
X=3/7
Answer:
[tex] - \frac{3}{7} [/tex]
Step-by-step explanation:
th first thing your gonna do is to multiply the number out side of each parentheses with the inside number. so 3 (3x-1)=9x-3 and 2 (3-x)= 6-2x. Now your equation 9x-3+6-2x=0. Then group all of the like terms. -3+6+9x-2x=0, -3+6=3 and 9x-2x=7x. 3+7x=0. Minus 7x on both sides to get rid of zero 3=-7x then divide by -7 to find x. 3 divide by -7 =
[tex] - \frac{3}{7 } [/tex]